Sistem Informasi Manajemen Bengkel Berbasis Web pada Bengkel Ikhsan Jaya Motor - Nurlaila, Dila; Mulyono, Herry (LPPM Universitas Dinamika Bangsa, 2023)
Management information systems as a tool to support productivity are needed both for large companies and small businesses, with the aim that business activities can run effectively and efficiently. Ikhsan Jaya Motor is one of the MSMEs (Ministry of Micro, Small & Medium Enterprises) engaged in motorcycle service, spare parts sales, motorcycle and car cleaning, and carpet cleaning. This study aims to analyze and design a web-based workshop management information system to overcome problems such as making financial reports, recording transaction data, and procuring stock of goods. The system development method used is RAD (Rapid Application Development) only for the stages requirements analysis, and systems design which is described with use cases, activity diagrams, and class diagrams. This research resulted in a prototype of a web-based workshop management information system in the form of a database design and a user interface design that was created using the prototype online tools Mockflow.